“…so it is very important…”: Evaluative Adjectives in Engineering Lectures - Noor Mala Ibrahim; Ummul Khair Ahmad (Kajian Malaysia, 2014)
Evaluation has been shown to have a prominent role in academic discourse and has been investigated in both written (Hyland, 1999) and spoken discourse (Swales and Burke, 2003; Crawford-Camiciottoli, 2004). In spoken discourse, particularly in academic lectures, evaluation is often used by lecturers to express their assessment of the content, and to orient listeners towards the preferred interpretation. This paper reports how lecturers from two different institutions (in Malaysia and in the UK) use adjectives of evaluation. Five engineering lectures with corresponding topic from each institution were analysed using Wordsmith Tools 5.0 (Scott, 2008), and extracted concordance lines containing adjectives of evaluation were manually examined to verify their evaluative function. Findings have revealed that lecturers from both institutions showed great awareness on the needs of their students in processing the lecture content, suggesting the fulfillment of their pedagogical role. However, the Malaysian lecturers used a limited variety of evaluative adjectives, with important being the most frequent. In contrast, their British counterparts employed a wider range of linguistic items to evaluate their discourse and at the same time, help students consider how to interpret the content of the lecture.